FAKTOR–FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PERUSAHAAN PADA SEKTOR INDUSTRI BARANG KONSUMSI DI BEI - Alpi, M Firza (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
This study aims to examine and analyze the effect of capital structure, company growth and profitability on firm value manufacturing companies listed on the indonesa stock exchange (BEI) for the 2017 – 2019 period. This study uses an associative approach. Data collection techniques in this study using dokumentation techniques. Data analysis techniques in this research are using desciptive statistical analysis, multiple linear regression analysis, classic assumption test, hypothesis test, and the coefficient of determination with a significance level of 5%. The results of this study indicate that the capital structure measured using the Debt to Equity Ratio (DER) has a negative and significant effect on firm value as measured by using the price book value (PBV). Company growth has a positive and insignificant effect on Price Book Value (PBV) and capital structure, company grwoth and profitability together have a significant effect on company value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017 – 2019 period.